Electricity-induced catalytic oxidation of RhB by O2 at a graphite anode. (10th March 2015) - Sun, Min; Liu, Yang; Xiang, Wei; Zhai, Lin-Feng
Graphical abstract: Highlights: Oxidation of RhB at the graphite anode of undivided electro-Fenton cell. O2 demonstrated enhancement on RhB degradation at the graphite anode. N, N-de-ethylation and cleavage of COC bonds happened on the RhB molecular. Unsaturated functional groups in graphite anode catalyzed oxidation of RhB by O2 . Anodic current was necessary to activate catalytic centers in graphite. Abstract: Undivided electro-Fenton cells are widely applied in wastewater treatment due to their high efficiencies in degrading hazardous pollutants. Anodic oxidation may play a role in the pollution removal in undivided electro-Fenton cells, which is usually ignored by researchers. In this work, the anodic oxidation possibly involved in undivided electro-Fenton cells was investigated with a graphite paper as the anode electrode and Rhodamine B (RhB) as the probe pollutant. Partial degradation of RhB was observed when an external voltage of + 2.0 V was applied to the graphite anode with continuous O2 supply. The degradation efficiency of RhB was enhanced by decreasing the pH of electrolyte. Total decolorization of RhB was achieved after 2 and 12 hrs of electrolysis at pH 3.0 and 6.8, respectively. Neither the direct oxidation nor the oxidation by reactive oxygen species mechanism was responsible for the degradation of RhB at the graphite anode. Alternatively, the anodic oxidation process was manipulated by the electro-oxidation of unsaturated functional groups in graphite. An anode-catalyzed O2 -oxidation pathway was proposed in which RhB was virtually oxidized by the O2, whereas the unsaturated functional groups in graphite played a catalyzing role. The anodic current was necessary to initiate such a reaction by activating the catalytic centers in these unsaturated functional groups.